Jacob A. Riis papers - Riis, Jacob A. (Jacob August), 1849-1914.
Correspondence, speeches, lectures, articles, appointment books, financial records, radio scripts, family papers, genealogical material, deeds, indentures, clippings, scrapbooks, printed matter, and other papers relating chiefly to Riis's work as a journalist documenting the plight of urban slum dwellers in New York, N.Y., culminating in his book, How the Other Half Lives (1890). Includes his reports for the Council of Confederated Good Government Clubs and the Small Parks Committee, New York, N.Y. Family correspondents include his wives, Elisabeth D. Nielson Riis and Mary Phillips Riis; his daughter, Kate Riis; his sons, John Riis and Roger William Riis; his grandson, J. Riis Owre; and his granddaughter, Martha Riis Moore. Other correspondents include Felix Adler, Andrew Carnegie, Josephine Shaw Lowell, Theodore Roosevelt, and Augustus Saint-Gaudens.
Microfilm edition available for a portion of the collection
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Journalist, author, and humanitarian.
Collection material in English, with Danish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adler, Felix, -- 1851-1933 -- Correspondence; Carnegie, Andrew, -- 1835-1919 -- Correspondence; Lowell, Josephine Shaw, -- 1843-1905 -- Correspondence; Moore, Martha Riis -- Correspondence; Owre, J. Riis -- Correspondence; Riis, Elisabeth D. Nielson, -- -1905 -- Correspondence; Riis, Kate -- Correspondence; Riis, John -- Correspondence; Riis, Mary Phillips -- Correspondence; Riis, Roger William, -- 1894- -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Saint-Gaudens, Augustus, -- 1848-1907 -- Correspondence; Riis family; Council of Confederated Good Government Clubs; Small Parks Committee (New York, N.Y.); Civic improvement -- New York (State) -- New York; Humanitarianism; Journalism -- New York (State) -- New York; Reformers; Slums -- New York (State) -- New York; Social history; Social problems; New York (N.Y.) -- Social conditions; Authors; Journalists; Philanthropists